2014
DOI: 10.1590/s1806-37132014000300009
|View full text |Cite
|
Sign up to set email alerts
|

Indoor air quality and health in schools

Abstract: Objective: To determine whether indoor air quality in schools is associated with the prevalence of allergic and respiratory diseases in children. Methods: We evaluated 1,019 students at 51 elementary schools in the city of Coimbra, Portugal. We applied a questionnaire that included questions regarding the demographic, social, and behavioral characteristics of students, as well as the presence of smoking in the family. We also evaluated the indoor air quality in the schools. Results: In the indoor air of the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…Natural ventilation usually has a low investment and operational costs, while mechanical ventilation systems are more expensive and consume energy . Although there are several guidelines and standards by reputable organizations such as WHO (World Health Organization) and ASHRAE (American Society of Heating, Refrigerating and Air‐Condition Engineers), as well as national building codes, these standards are not always met: many studies from different countries have shown ventilation to be inadequate in a large proportion of classrooms . The reasons could be related to overcrowding in classrooms, as well as the type and condition of the school building and the ventilation system …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural ventilation usually has a low investment and operational costs, while mechanical ventilation systems are more expensive and consume energy . Although there are several guidelines and standards by reputable organizations such as WHO (World Health Organization) and ASHRAE (American Society of Heating, Refrigerating and Air‐Condition Engineers), as well as national building codes, these standards are not always met: many studies from different countries have shown ventilation to be inadequate in a large proportion of classrooms . The reasons could be related to overcrowding in classrooms, as well as the type and condition of the school building and the ventilation system …”
Section: Introductionmentioning
confidence: 99%
“…37 Although there are several guidelines and standards by reputable organizations such as WHO (World Health Organization) and ASHRAE (American Society of Heating, Refrigerating and Air-Condition Engineers), as well as national building codes, these standards are not always met: many studies from different countries have shown ventilation to be inadequate in a large proportion of classrooms. 31,[38][39][40][41] The reasons could be related to overcrowding in classrooms, as well as the type and condition of the school building and the ventilation system. 42,43 Traditionally, natural ventilation has been utilized to dilute and remove the build-up of indoor pollutants.…”
mentioning
confidence: 99%
“…Research conducted by Panayostis in 2001 reports that students with high CO 2 concentration tend to feel drowsy, lethargic, and complaining about stuffiness or stale air (Mahyuddin & Awbi, 2012). The have respiratory symptoms such as sneezing, wheezing, rhinitis and asthma (Ferreira & Cardoso, 2014) and a positive trend between CO 2 in the room and asthma prevalence shows 4.7% (Martins et al, 2014). Research in Canada indicates that exposure to 10 types of indoor VOC is associated with reduced pulmonary function especially in the age group below 17 (Cakmak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A review study conducted by Daisy et al [59], found that classroom ventilation is typically inadequate and may exacerbate children’s exposure to indoor air pollutants. A more recent study conducted in 2014 by Ferreira et al [60 ▪ ], corroborated these findings and showed a significant proportion of carbon dioxide measurements in urban schools in Portugal were above 1000 parts/million (ppm), the threshold generally regarded as indicative of unacceptable ventilation rates. The study conducted by Ferreira et al [60 ▪ ], also demonstrated that lack of concentration and attention was associated with CO 2 concentrations above the maximum recommended level in indoor air ( P = 0.002).…”
Section: Reviewmentioning
confidence: 79%